Characterisation of IL-15 and IL-2Rβ in grass carp: IL-15 upregulates cytokines and transcription factors of type 1 immune response and NK cell activation. Issue 107 (December 2020) - Wang, Wei; Wang, Junya; Lei, Lina; Xu, Jiawen; Qin, Yuting; Gao, Qian; Zou, Jun
Abstract: Interleukin (IL) −15 belongs to the common cytokine receptor γ chain (γC) family and has diverse functions in regulating the development, proliferation and activation of NK and T cells. It activates a hetero-trimeric receptor complex consisting of IL-2Rα, IL-2Rβ and a common γ chain (γC). In this study, the full-length cDNA sequences of IL-15 and IL-2Rβ were identified in grass carp ( Ctenopharyngodon idella, Ci ) and their expression profiles analysed. The Ci IL-15 and Ci IL-2Rβ were shown to be broadly expressed in tissues, with the highest levels detected in the spleen. Moreover, the Ci IL-15 and Ci IL-2Rβ were modulated in primary head kidney leucocytes (HKLs) and splenocytes by immunostimulants and cytokines, and in the head kidney and spleen of fish after infection of Flavobacterium columnare and grass carp reovirus. The bioactivity of bacteria derived recombinant Ci IL-15 protein was evaluated in the primary leucocytes. The Ci IL-15 was shown to induce signature genes of type 1 immune response (IFN-γ and T-bet) and NK cell activation (perforin and Eomesa), whilst exhibiting inhibitory effects on the genes involved in the type 2 immune response (IL-4/ 13, IL-10 and Gata3). Our data suggest that IL-15 is a key regulator in promoting the type 1 immune response and NK cell activation in fish. Highlights: Homologues of IL-15 and IL-2Rβ were identified in grass carp. Ci IL-15 and Ci IL-2Rβ were upregulated in the spleen and head kidney after bacterial and viral infection. Ci IL-15 upregulated signature genes of type 1 immune response and NK cell activation in primary leucocytes. Ci IL-15 inhibited genes involved in type 2 immune response.